Inclusion complexes of 2-methoxyestradiol with dimethylated and permethylated β-cyclodextrins: models for cyclodextrin–steroid interaction - Caira, Mino R.; Bourne, Susan A.; Samsodien, Halima; Smith, Vincent J. (Beilstein Journal of Organic Chemistry, 2015)
The interaction between the potent anticancer agent 2-methoxyestradiol (2ME) and a series of cyclodextrins (CDs) was investigated in the solid state using thermal analysis and X-ray diffraction, while the possibility of enhancing its poor aqueous solubility with CDs was probed by means of equilibrium solubility and dissolution rate measurements. Single crystal X-ray diffraction studies of the inclusion complexes between 2ME and the derivatised cyclodextrins heptakis(2,6-di-O-methyl)-β-CD (DIMEB) and heptakis(2,3,6-tri-O-methyl)-β-CD (TRIMEB) revealed for the first time the nature of the encapsulation of a bioactive steroid by representative CD host molecules. Inclusion complexation invariably involves insertion of the D-ring of 2ME from the secondary side of each CD molecule, with the 17-OH group generally hydrogen bonding to a host glycosidic oxygen atom within the CD cavity, while the A-ring and part of the B-ring of 2ME protrude from the secondary side. In the case of the TRIMEB·2ME complex, there is evidence that complexation proceeds with mutual conformational adaptation of host and guest molecules. The aqueous solubility of 2ME was significantly enhanced by CDs, with DIMEB, TRIMEB, randomly methylated β-CD and hydroxypropyl-β-CD being the most effective hosts. The 2:1 host–guest β-CD inclusion complex, prepared by two methods, yielded very rapid dissolution in water at 37 °C relative to untreated 2ME, attaining complete dissolution within 15 minutes (co-precipitated complex) and 45 minutes (complex from kneading).
Keywords: complexation; cyclodextrin; 2-methoxyestradiol; solubility; X-ray diffraction

(untitled) - Sawada, T.; Hisada, H.; Fujita, M. (J. Am. Chem. Soc., 2014)

(untitled) - Dubey, R. K.; Imthurn, B.; Jackson, E. K. (Endocrinology, 2007)

(untitled) - Verenich, S.; Gerk, P. M. (Mol. Pharmaceutics, 2010)

(untitled) - LaVallee, T. M.; Burke, P. A.; Swartz, G. M.; Hamel, E.; Agoston, G. E.; Shah, J.; Suwandi, L.; Hanson, A. D.; Fogler, W. E.; Sidor, C. F.; Treston, A. M. (Mol. Cancer Ther., 2008)

(untitled) - Peyrat, J.-F.; Brion, J.-D.; Alami, M. (Curr. Med. Chem., 2012)

(untitled) - Kulke, M. H.; Chan, J. A.; Meyerhardt, J. A.; Zhu, A.; Abrams, T. A.; Blaszkowsky, L. S.; Regan, E.; Sidor, C.; Fuchs, C. S. (Cancer Chemother. Pharmacol., 2011)

(untitled) - Bruce, J. Y.; Eickhoff, J.; Pili, R.; Logan, T.; Carducci, M.; Arnott, J.; Treston, A.; Wilding, G.; Liu, G. (Invest. New Drugs, 2012)

(untitled) - Leese, M. P.; Leblond, B.; Smith, A.; Newman, S. P.; Di Fiore, A.; De Simone, G.; Supuran, C. T.; Purohit, A.; Reed, M. J.; Potter, B. V. L. (J. Med. Chem., 2006)

(untitled) - Caira, M. R.; Bourne, S. A.; Samsodien, H. (J. Pharm. Sci., 2015)

(untitled) - Pinto, M. P.; Medina, R. A.; Owen, G. I. (Horm. Cancer, 2014)

Supramolecular derivatives of selected bioactive compounds: a physicochemical study - Samsodien, H. (Department of Chemistry, University of Cape Town, 2010)

(untitled) - Frömming, K.-H.; Weyermann, I. (Arch. Pharm., 1972)

(untitled) - Frömming, K.-H.; Weyermann, I. (Arzneim. Forsch., 1973)

(untitled) - Uekama, K.; Fujinaga, T.; Hirayama, F.; Otagiri, M.; Yamasaki, M. (Int. J. Pharm., 1982)

(untitled) - Vergeichik, Y. N.; Kompantseva, Y. V.; Gavrilin, M. V.; Ovcharenko, L. P. (Khim.-Farm. Zh., 1993)

Cambridge Structural Database and Cambridge Structural Database system, Version 5.36 (Cambridge Crystallographic Data Centre, University Chemical Laboratory, 2015)

(untitled) - Bom, A.; Bradley, M.; Cameron, K.; Clark, J. K.; van Egmond, J.; Feilden, H.; MacLean, E. J.; Muir, A. W.; Palin, R.; Rees, D. C.; Zhang, M.-Q. (Angew. Chem., Int. Ed., 2002)

(untitled) - de Boer, H. D. (J. Crit. Care, 2009)

(untitled) - Volkov, S.; Kumprecht, L.; Buděšínský, M.; Lepšík, M.; Dušek, M.; Kraus, T. (Org. Biomol. Chem., 2015)

(untitled) - Caira, M. R. (Rev. Roum. Chim., 2001)

(untitled) - Caira, M. R.; Bourne, S. A.; Mhlongo, W. T.; Dean, P. M. (Chem. Commun., 2004)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A, 2008)

(untitled) - Aree, T.; Saenger, W.; Leibnitz, P.; Hoier, H. (Carbohydr. Res., 1999)

Inclusion Compounds - Sanger, W. (Academic Press, 1984)

(untitled) - Steiner, T.; Saenger, W. (Carbohydr. Res., 1995)

(untitled) - Trollope, L.; Cruickshank, D. L.; Noonan, T.; Bourne, S. A.; Sorrenti, M.; Catenacci, L.; Caira, M. R. (Beilstein J. Org. Chem., 2014)

Cyclodextrins in Pharmacy - Frömming, K.-H.; Szejtli, J. (Springer, 1994)

New Trends in Cyclodextrins and Derivatives - Schmid, G. (Chapter 1, 1991)

Draft Report EMA/CHMP/333892/2013: Background review for cyclodextrins used as excipients - European Medicines Agency, Committee for Human Medicinal Products (CHMP)

(untitled) - Makedonopoulou, S.; Yannakopoulou, K.; Mentzafos, D.; Lamzin, V.; Popov, A.; Mavridis, I. M. (Acta Crystallogr., 2001)

Digital Solutions for Imaging and Microscopy, Version 3.1 for Windows (Soft Imaging System GmbH, 2000)

(untitled) - Barbour, L. J. (J. Supramol. Chem., 2001)